The Effect Of COVID-19 Spread On Stock Markets: The Case Of Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study attempts to investigate the effects of the COVID-19 spread on the Syrian financial market (Damascus Securities Exchange). The study applied the Simple Regression Model to investigate the impact of the COVID-19 on the trading value of Damascus Securities Exchange during the period dated from 30th March to 28th July. The period of the study is 121 days, the researcher excluded holidays and the suspension of work in the Damascus Securities Exchange due to quarantine, therefore, the number of views decreased from (121) views to (54) views.  The study assumes the COVID-19 confirmed cases and death cases to be the independent variables, and the trading value of the Damascus Securities Exchange the dependent variable.To achieve the objective of the study, the researcher used a hypothetical-deductive approach to formulate the hypotheses, then in order to test these hypotheses, the researcher used panel data (data time series).The study findings revealed that there is a negative significant relationship between both of the confirmed cases and the death cases from COVID-19, and the trading value of Damascus Securities Exchange from 30th March 2020 to 28th July 2020.